1996
DOI: 10.1115/1.2817368
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: The Experimentalist and the Problem of Turbulence in the Age of Supercomputers

Abstract: Due to the rising capabilities of computational fluid mechanics ( CFD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…However, experience showed that in order to study new phenomena experiments are still the most economical approach. The CFD codes, once validated against experimental data, are the most effective tool for the production of data to build a comprehensive flow database (Gharib, 1996).…”
Section: Integrated Approach With Quantitative Flow Field Visualizatimentioning
confidence: 99%
“…However, experience showed that in order to study new phenomena experiments are still the most economical approach. The CFD codes, once validated against experimental data, are the most effective tool for the production of data to build a comprehensive flow database (Gharib, 1996).…”
Section: Integrated Approach With Quantitative Flow Field Visualizatimentioning
confidence: 99%
“…Yeh and Cummins 6 and Cummins et al 5 originated the idea of using the Doppler shift in the frequency of the light scattered by particles or molecules in the ow to measure the ow velocity. The Doppler shift equation is given by (1) where s is the unit vector toward the observer/detector, o is the unit vector in the propagation direction of the laser light, V is the velocity vector of the light-scattering uid element/particle, and k is the wavelength of the laser light (refer to Fig. 1).…”
Section: Doppler Shiftmentioning
confidence: 99%
“…Numerical or computational fluid dynamic (CFD) modelling schemes of full scale aircraft have advanced substantially since the 1970's but assumptions must still be made. For example, if a complete solution of the Navier Stokes equations was to be obtained, a direct numerical simulation (DNS) would be required where the mesh density scales with Reynolds number Re 9/4 [4]. Therefore, given large civilian aircraft have Reynolds numbers based on wing chord in excess of 10 million, three dimensional mesh sizes in excess of 1 x 10 15 cells would be needed for a DNS model.…”
Section: Introductionmentioning
confidence: 99%